PERANCANGAN MODEL BISNIS STARTUP APLIKASI DIGITAL UNTUK PENGELOLAAN DAN PROMOSI COFFEE SHOP DI KOTA JEMBER DENGAN MENGGUNAKAN METODE LEAN STARTUP DAN SERVICE DESIGN - Ervian Akbarsyah Mahendra; A.A.B. Dinariyana DP; Dyah Santhi Dewi (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
The rapid development of digital technology has encouraged business actors to improve operational efficiency, promotion, and customer experience through application-based services. However, coffee shops in Jember City still face various challenges, including limited promotional reach, low customer loyalty, the absence of integrated reservation systems, and minimal service personalization. This study aims to design a business model and a digital application prototype for coffee shops by applying the Lean Canvas framework, the Lean Startup approach through the Build–Measure–Learn cycle, and service design using the Double Diamond framework at the Define, Develop, and Deliver stages. The findings indicate that coffee shop managers require features for transaction recording, inventory management, promotion, customer loyalty programs, reservations, financial reporting, and business performance analysis, while customers need access to coffee shop catalogs, promotional information, personalized recommendations, rewards, convenient reservation features, and interactive feedback. The prototype was evaluated using the System Usability Scale (SUS) with two user groups, resulting in scores of 89 for customers and 88 for managers, which fall into the A+ (Excellent), Acceptable, and Promoter categories. These results demonstrate high usability and indicate strong potential for implementing the application to support the digitalization of the local coffee shop ecosystem in Jember City. Keywords: Startup Business Model, Digital Application, Coffee Shop, Lean Startup, Service Design